2016
DOI: 10.1111/cmi.12576
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular traffic of the lysine and glutamic acid rich protein KERP1 reveals features of endomembrane organization inEntamoeba histolytica

Abstract: The development of amoebiasis is influenced by the expression of the lysine and glutamic acid rich protein 1 (KERP1), a virulence factor involved in Entamoeba histolytica adherence to human cells. Up to date, it is unknown how the protein transits the parasite cytoplasm towards the plasma membrane, specially because this organism lacks a well-defined endoplasmic reticulum (ER) and Golgi apparatus. In this work we demonstrate that KERP1 is present at the cell surface and in intracellular vesicles which traffic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
(101 reference statements)
1
16
0
Order By: Relevance
“…Phagocytosis is one of the main functions expressed during destruction of the epithelia by the trophozoites. Membrane proteins participating in these events have been already identified, among them the Gal/GalNac lectin (Petri, Haque, & Mann, ), the EhCPADH complex (Garcia‐Rivera et al, ), the KERP1 protein (Perdomo et al, ), and others (Garcia‐Rivera et al, ; Laughlin & Temesvari, ; Pillai & Kain, ). EhCPADH is formed by the proteins EhCP112 (446 amino acids) and EhADH (687 amino acids), which belongs to the ALIX family.…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytosis is one of the main functions expressed during destruction of the epithelia by the trophozoites. Membrane proteins participating in these events have been already identified, among them the Gal/GalNac lectin (Petri, Haque, & Mann, ), the EhCPADH complex (Garcia‐Rivera et al, ), the KERP1 protein (Perdomo et al, ), and others (Garcia‐Rivera et al, ; Laughlin & Temesvari, ; Pillai & Kain, ). EhCPADH is formed by the proteins EhCP112 (446 amino acids) and EhADH (687 amino acids), which belongs to the ALIX family.…”
Section: Introductionmentioning
confidence: 99%
“…histolytica ALIX family protein) [25] inside phagolysosomes and multivesicular bodies (MVB) [26]. Though, we do not discard the participation of other Alix proteins involved in endomembrane trafficking [27, 28]. Thus, it is plausible to assume that the “hand-off” model, “NPC2-NPC1-cholesterol-NPC2-NPC1” proposed for mammalian cells, could also be functioning in trophozoites to first carry exogenous cholesterol inside the cell and then, to transport it to distinct organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there is an active engagement of the E. histolytica cytoskeleton to provide backup for the amoebic survival functions (i.e., motility, erythrophagocytosis) and, more likely, although not yet explored, a relevant role in the endomembrane dynamics. Experiments have shown that there is an active engagement from the cytoskeleton and secretion pathway to deliver virulence factors to the plasma membrane, even under chemical stress conditions [ 69 , 87 ]. This process is contrary to what is detailed in mammalian cells, where the ER limits the folding and secretion when under stress to prevent ER overload.…”
Section: Discussionmentioning
confidence: 99%
“…Motility is an essential function for the survival of E. histolytica [ 67 , 68 ] not only for displacement and phagocytosis of host cells, but also for the intracellular trafficking of virulence factors [ 69 ]. Another project correlating the transcriptomic data of NO-exposed parasites to the proteomic data of NO-adapted trophozoites [ 70 ] showed an up-regulation in the gene expression of cytoskeleton proteins that were previously identified by proteomics.…”
Section: E Histolytica Endomembrane Network Ismentioning
confidence: 99%